Low preoperative hematocrit adversely affects short-term outcomes after arthroscopic rotator cuff repair - Noah Kim, BS; Kenny Ling, MD; Katherine Wang, BA; David E. Komatsu, PhD; Edward D. Wang, MD (JSES Reviews, Reports, and Techniques)
Background: The purpose of this study was to investigate preoperative anemia as a risk factor for postoperative complications after arthroscopic rotator cuff repair (ARCR). Methods: Adult patients who underwent ARCR from 2015-2020 were identified in the American College of Surgeons National Surgical Quality Improvement Program database. Patients were grouped according to the following preoperative hematocrit levels: normal (male >39%, female >36%), mild anemia (male 33%-39%, female 33%-36%), and moderate to severe anemia (male and female ≤33%). Multivariable logistic regression analyses were performed to identify significant differences in 30-day postoperative complication rates. Results: Of the 21,836 patients identified, 19,726 (90.3%) patients had normal preoperative hematocrit, 1731 (7.9%) were mildly anemic, and 379 (1.7%) were moderate to severely anemic. After adjusting for significantly associated demographics and comorbidities, mild anemia was a significant predictor of any complication (odds ratio [OR] 1.436, P = .007), cardiac complications (OR 4.891, P = .002) sepsis-related complications (OR 4.760, P = .004), readmission (OR 1.585, P = .014), and nonhome discharge (OR 1.839, P = .006). Moderate to severe anemia was a significant predictor of any complication (OR 2.471, P < .001), readmission (OR 3.002, P < .001), and nonhome discharge (OR 3.211, P < .001). Conclusion: Preoperative anemia is a significant risk factor for postoperative complications within 30 days of ARCR.